2018
DOI: 10.4103/ijmm.ijmm_17_258
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Circulating Human Adenovirus Types in Acute Conjunctivitis Cases in Chandigarh, North India

Abstract: Human adenovirus (HAdV) is a major cause of viral conjunctivitis. The various serotypes implicated in the causation are 3, 4, 8, 19 and 37. The present study aimed to know the circulating types of HAdV causing acute conjunctivitis in North India. A total of 23 conjunctival swabs were collected from patients with clinically suspected acute viral conjunctivitis during 2014-2015. The HAdV was implicated in the etiology in 65.2% of cases. The sequencing of representative samples using hexon gene suggests the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The involvement of only one eye is seen which can be due to that the patient visit the OPD before the involvement of the other eye. A study conducted by Mini P. Singh, Jagat Ram, 1 Archit Kumar, Tripti Rungta, Amit Gupta, 1 Jasmine Khurana, Radha Kanta Ratho in Chandigarh, India in Jan-March 2018 showed that conjunctivitis was unilateral in 12 patients (52.2%) and bilateral in 11 patients (47.8%) 8 In our study out of 52 patients 23 patients had preauricular lymphadenopathy which is 44% and 47 patients had no preauricular lymphadenopathy which is 56 %. A similar finding was noted in a study done by Balasopoulou et al during March 2012 to June 2012 which shows that out of 231 cases of conjunctivitis preauricular lymphadenopathy was evident in 125 cases which is 54.2% 9 According to our study acute conjunctivitis was observed in low socioeconomic patients as compare to middle socioeconomic status.…”
Section: Graph 2: Socioeconomic Distributionmentioning
confidence: 45%
“…The involvement of only one eye is seen which can be due to that the patient visit the OPD before the involvement of the other eye. A study conducted by Mini P. Singh, Jagat Ram, 1 Archit Kumar, Tripti Rungta, Amit Gupta, 1 Jasmine Khurana, Radha Kanta Ratho in Chandigarh, India in Jan-March 2018 showed that conjunctivitis was unilateral in 12 patients (52.2%) and bilateral in 11 patients (47.8%) 8 In our study out of 52 patients 23 patients had preauricular lymphadenopathy which is 44% and 47 patients had no preauricular lymphadenopathy which is 56 %. A similar finding was noted in a study done by Balasopoulou et al during March 2012 to June 2012 which shows that out of 231 cases of conjunctivitis preauricular lymphadenopathy was evident in 125 cases which is 54.2% 9 According to our study acute conjunctivitis was observed in low socioeconomic patients as compare to middle socioeconomic status.…”
Section: Graph 2: Socioeconomic Distributionmentioning
confidence: 45%
“…In India, several outbreaks of EKC have been observed, with HAdV-8 being the most common causative agent [24], along with others like HAdV-6 and HAdV-2 [25]. In our previous published report based on sequencing the partial region of hexon we found the isolates to be closer to HAdV-54 than HAdV-8 phylogenetically [26].…”
Section: Introductionmentioning
confidence: 55%
“…However, 80% of acute cases are caused by viruses [7,9,15] . These include Adenovirus, Herpes simplex virus, Varicella-zoster virus, Enterovirus70, and CoxsackieA24 [15,18] . Human Adenovirus (HAdV) causes 65%-90% of viral conjunctivitis cases [9,18] .…”
Section: Epidemiologymentioning
confidence: 99%